Impacts of Soil and Water Management Measures on Crop Production and Farm Income of Rural Households in the Damota Area Districts, Southern Ethiopia - Mamush Masha; Teshome Yirgu; Mulugeta Debele (International Journal of Agronomy)
Improving crop productivity and farm income of rural households and ensuring food security through soil and water conservation (SWC) measures are one of the integral parts of sustainable livelihood approaches. The study aims to assess the impact of soil and water conservation measures on improving the rural livelihoods, which is measured in terms of annual crop production and farm income of rural households in the Damota area districts. The data was collected from 378 households (209 adopters and 169 nonadopters of SWC measures) using survey questionnaires, which were randomly chosen by using multistage sampling techniques. Descriptive and inferential statistics with propensity score matching (PSM) method were used to analyze the collected data. The propensity score matching method was used to assess the impacts of soil and water conservation measures by controlling unobserved heterogeneity and were matched with balanced observable characteristics. The result showed that the mean value of wheat production of adopter households was higher (654 kilograms per hectare) than that of nonadopters (496 kilograms per hectare). Similarly, the mean values of farm income of adopter households were higher (17372.67 Ethiopian Birr per year) than those of nonadopter households (13883.22 Ethiopian Birr per year). The result indicated that both crop production and annual farm income were more pronounced when farmers implemented sustainable soil and water conservation measures on their farming lands. This suggests that all rural households need to focus on the large-scale adoption, integration, and maintenances of damaged structures for better agricultural outcomes.